Analyzing The Factors Shaping Coriolanus Snow's Ambition in “The Ballad of Songbirds and Snakes” Novel by Suzanne Collins - Abdullah, Reflan; Balango, Mery; Katili, Adriansyah A. (Transbahasa, 2024)
This study aims to analyze Coriolanus Snow's ambition and the factors that shape it in Suzanne Collins'